Organization and Microanatomy of the Sclerolinum contortum Trophosome (Polychaeta, Siboglinidae) - Eichinger, Irmgard; Klepal, Waltraud; Schmid, Markus; Bright, Monika (BIOLOGICAL BULLETIN, 2011)
The trophosome-an organ especially evolved to accommodate symbiotic bacteria-is a key character of the polychaete family Siboglinidae. Astonishingly, the trophosomes vary in organization and origin between the different siboglinid taxa. The trophosome of the small genus Sclerolinum was nearly unknown until now. Here we investigated the trophosome of S. contortum from the Gulf of Mexico, using light and electron microscopy. We show that this organ derives from the visceral mesoderm and propose that the trophosome of the sister clade Vestimentifera and Sclerolinum is a homologous character. Like that of juvenile vestimentiferans, the trophosome of Sclerolinum trophosome is simply organized. This study reveals that the Sclerolinum trophosome exhibits two regions that differ in the organization of host tissue and the size and shape of the symbionts. We suggest that a specific cell cycle within the symbiont-housing organ is directed along the longitudinal body axis, with a region of proliferation anteriorly and a region of degradation posteriorly. Using Raman microspectroscopy we demonstrate that the endosymbionts of S. contortum from the Gulf of Mexico contain sulfur vesicles, and we argue for a chemoautotrophic sulfur-oxidizing metabolism.
Keywords: ROV Jason (Remotely Operated Vehicle)